Optimalisasi Dana BOSP untuk Pemberdayaan Pendidikan Masyarakat di PKBM Wilayah Surabaya - Dewi, Dyah Purnama Tri Utami; Nofiyanti, Tia; Asmi, Nurul; Arisman, Arisman; Purwanto, Purwanto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study investigates the optimization strategies of School Operational Assistance Funds (BOSP) in enhancing community education empowerment through Community Learning Centers (PKBM) in Surabaya. Despite BOSP’s potential as a public funding mechanism, many PKBMs face persistent issues such as weak managerial capacity, delayed fund disbursement, and inadequate financial reporting systems. The study aims to fill this research gap by analyzing how participatory and transparent fund management contributes to community empowerment. Using a descriptive qualitative approach, data were collected from 18 informants consisting of PKBM managers, tutors, and learners across four BOSP-recipient PKBMs through in-depth interviews, field observations, and document reviews. The findings reveal that PKBMs allocating BOSP towards functional skill training such as sewing, entrepreneurship, and digital literacy successfully enhanced learners’ economic and social capacities. Moreover, institutions that adopted transparent financial reporting and community-based planning fostered higher participation and accountability. However, structural challenges remain, particularly in standardizing reporting systems and improving managerial skills. This study contributes to the literature by highlighting BOSP’s role not merely as an operational budget but as a strategic instrument for social transformation, emphasizing digital accountability and inclusive participation as prerequisites for sustainable non-formal education governance.